The Influence Of Communication In Organizations For The Success Of Working In The Department Of Manpower Bone District - Musliamin Musliamin (Palakka : Media and Islamic Communication, 2020)
This study discusses "The Influence of Communication in the Organization for the Smoothness of Work in the Manpower Office of Bone Regency". The purpose of this study was to obtain an objective picture of the effect of communication in order to improve the performance of the employees of the Bone Regency Manpower Office. This study uses field research methods (field research), namely the method used by conducting research on the object under study with the method of interviewing, observation and documentation. The data source in this study were employees of the Bone Regency Manpower Office. The data that has been collected from the research results were analyzed using qualitative descriptive analysis techniques. The results showed that, 1). The conditions of the implementation of organizational communication in supporting the smooth implementation of tasks within the Bone Regency Manpower Office, 2). the effectiveness of the communication carried out, and what factors underlie its implementation. 3). the relationship between the implementation of communication with the smooth completion of organizational tasks.